Facile Synthesis of Novel Benzoylthiophene C-Nucleoside Analogues via Coupling of Sugar Alkynes, Aroyl Chlorides, and 1,4-Dithiane-2,5-diol - Luo, Yang; Gao, Fei; Liu, Hong; Zhang, Fuyi; Zhao, Yufen (Synthesis, 2020)
Concise synthesis of novel benzoylthiophene C-nucleoside analogues has been achieved by the reaction of various terminal sugar alkynes with substituted benzoyl chlorides and 1,4-dithiane-2,5-diol, and subsequent dilute HCl-promoted dehydration in one pot. The sugar alkynes include pyranosides, furanosides, and acyclic sugar. The benzoyl chloride has various substituents. Twenty-eight examples are given. The desired products are obtained in 70–89% yields, and the mechanism has been clarified by isolation of the intermediate.
Keywords: C-nucleoside; analogue; sugar; alkyne; thiophene; heterocycle